Optical elements based on silicon photonics - Butt, M.A.; Khonina, S.N.; Kazanskiy, N.L. (Kompʹûternaâ optika, 2019)
Silicon photonics is gaining substantial impulse because it permits optical devices to be realized inexpensively using standard semiconductor fabrication techniques and integrated with microelectronic chips. In this paper, we designed few optical elements such as optical power splitter, polarization beam splitter and Bragg grating based on silicon platform simulated using finite element method.